2012
DOI: 10.1002/anie.201203754
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of Substrates for Zinc‐dependent Lysine Deacylase Enzymes: HDAC3 Exhibits Decrotonylase Activity In Vitro

Abstract: Systematic screening of the activities of the eleven human zinc-dependent lysine deacylases against a series of fluorogenic substrates as well as kinetic evaluation revealed substrates for screenings of histone deacetylases HDAC10 and HDAC11 at reasonably low enzyme concentrations. Furthermore, HDAC3 in complex with nuclear receptor corepressor 1 (HDAC3-NCoR1) was shown to harbor decrotonylase activity in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
78
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 105 publications
(87 citation statements)
references
References 52 publications
9
78
0
Order By: Relevance
“…For example, many other endogenous acyl-lysine modifications have been validated, including propionylation, butyrylation, crotonylation, and glutarylation. Importantly, these modifications can be removed by HDACs and sirtuins in vitro (Feldman et al, 2013; Madsen and Olsen, 2012). Additionally, longer chain acyl-lysine modifications occur in cells and are targeted for removal by SIRT6 in vivo (Jiang et al, 2013).…”
Section: Carbon Stress and Sirtuin-mediated Protein Quality Controlmentioning
confidence: 99%
“…For example, many other endogenous acyl-lysine modifications have been validated, including propionylation, butyrylation, crotonylation, and glutarylation. Importantly, these modifications can be removed by HDACs and sirtuins in vitro (Feldman et al, 2013; Madsen and Olsen, 2012). Additionally, longer chain acyl-lysine modifications occur in cells and are targeted for removal by SIRT6 in vivo (Jiang et al, 2013).…”
Section: Carbon Stress and Sirtuin-mediated Protein Quality Controlmentioning
confidence: 99%
“…However, further mechanistic and functional studies of histone Kcr have been limited by a lack of knowledge of the enzymes that catalyze the addition or removal of Kcr in cells. In a systematic screening of the activities of the 11 human zinc-dependent lysine deacetylases (i.e., HDAC1–HDAC11) against a series of C-terminal lysine acylated peptides, Olsen et al found that HDAC3 in complex with nuclear receptor corepressor 1 (HDAC3–NCoR1) had detectable decrotonylase activity towards a model peptide substrate in a fluorometric assay (Madsen and Olsen, 2012). Recently, using a radioactive thin layer chromatography based assay, Denu et al demonstrated that Sirt1 and Sirt2 can catalyze the removal of a crotonyl group from a histone H3K9Cr peptide (Feldman et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…3,[5][6][7][8][9] While the former family members achieve deacylation via a Zn 2+ -assisted hydrolysis of the side chain amide bond of N e -acyl-lysine, sirtuins employ a unique b-NAD + -dependent strategy to achieve deacylation in that N e -acyl-lysine is condensed with b-NAD + with the formation of three products in the same reaction, that is, nicotinamide, deacylated product, and 2 0 -O-AADPR (Fig. 1).…”
mentioning
confidence: 99%
“…The chemical structures of the four further derivatives(19)(20)(21)(22) designed from a structure-activity-relationship analysis of the initial 16 derivatives(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18).…”
mentioning
confidence: 99%
See 1 more Smart Citation